Does the Defining Issues Test Measure Ethical Judgment Ability or Political Position? - Bailey, CharlesD. (Journal of Social Psychology, 2011)
This article addresses the construct validity of the Defining Issues Test of ethical judgment (DIT/DIT-2). Alleging a political bias in the test, Emler and colleagues (1983, 1998, 1999, 2007), show that conservatives score higher when asked to fake as liberals, implying that they understand the reasoning associated with 'higher' moral development but avoid items they see as liberally biased. DIT proponents challenge the internal validity of faking studies, advocating an explained-variance validation. This study takes a new approach: Adult participants complete the DIT-2, then evaluate the raw responses of others to discern political orientation and ethical development. Results show that individuals scoring higher on the DIT-2 rank others' ethical judgment in a way consistent with DIT-2-based rankings. Accuracy at assessing political orientation, however, is low. Results support the DIT-2's validity as a measure of ethical development, not an expression of political position.